Effect of interventions for the well-being, satisfaction and flourishing of general practitioners—a systematic review - Nick Glozier; Ian B Hickie; Diana Naehrig; Aaron Schokman; Jessica Kate Hughes; Ronald Epstein (BMJ Open)
Objectives Clinician well-being has been recognised as an important pillar of healthcare. However, research mainly addresses mitigating the negative aspects of stress or burnout, rather than enabling positive aspects. With the added strain of a pandemic, identifying how best to maintain and support the well-being, satisfaction and flourishing of general practitioners (GPs) is now more important than ever.Design Systematic review.Data sources We searched MEDLINE, PsycINFO, Embase, CINAHL and Scopus from 2000 to 2020.Study selection Intervention studies with more than 50% GPs in the sample evaluating self-reported well-being, satisfaction and related positive outcomes were included. The Cochrane Risk of Bias 2 tool was applied.Results We retrieved 14 792 records, 94 studies underwent full-text review. We included 19 studies in total. Six randomised controlled trials, three non-randomised, controlled trials, eight non-controlled studies of individual or organisational interventions with a total of 1141 participants. There were two quasi-experimental articles evaluating health system policy change. Quantitative and qualitative positive outcomes were extracted and analysed. Individual mindfulness interventions were the most common (k=9) with medium to large within-group (0.37–1.05) and between-group (0.5–1.5) effect sizes for mindfulness outcomes, and small-to-medium effect sizes for other positive outcomes including resilience, compassion and empathy. Studies assessing other intervention foci or other positive outcomes (including well-being, satisfaction) were of limited size and quality.Conclusions There is remarkably little evidence on how to improve GPs well-being beyond using mindfulness interventions, particularly for interventions addressing organisational or system factors. This was further undermined by inconsistent reporting, and overall high risk of bias. We need to conduct research in this space with the same rigour with which we approach clinical intervention studies in patients.PROSPERO registration number CRD42020164699.Funding source Dr Diana Naehrig is funded through the Raymond Seidler PhD scholarship.